STUDY ON GROWTH RATE OF MALE RABBITS (Lepus negricollis) FED DIFFERENT LEVELS OF FERMENTED COFFEE PULP - Budiari, Ni Luh Gede; Mastika, I Made; Nuriyasa, I Made (E-Journal Of Animal Science Udayana University; Vol 3, No 2, Tahun 2014)
A study on growth rate of male rabbit fed different levels of fermented coffee pulp was carried out at Gulingan village, Mengwi, Badung regency, Bali province from August to October 2013. A Randomized Block Design (RBD) with five treatments and eight replicates in each treatment was used in this experiment.  The treatment were diet  without coffee  pulp (R0),  diet with 10%  unfermented coffee pulp (R1), diet with 20% unfermented coffee pulp (R2), diet with 10% fermented coffee pulp (R3), and diet with 20% fermented coffee pulp (R4). Each treatment consisted of 8 male five week old local rabbits as replication. Variables observed were final body weight, weight gain, feed intake, water consumption, feed efficiency, dry matter, energy and protein digestibility. The results showed that rabbits  given ration with 10% fermented coffee pulp (R3) revealed has higher dry matter energy and protein digestibility. Further, that had highest final body weight, weight gain and highest feed efficiency. From the result of the experiment can the  concluded that the use of 10% fermented coffee pulp in the diet produced the highest performance (P<0,05)  compared to other treatments. The use of fermented coffee  pulp 10% could be recommended to farmers for substituting rice brand in rabbits diets.
Keywords: rabbits growth, coffee pulp, fermentation